2019
DOI: 10.1098/rsos.181764
|View full text |Cite
|
Sign up to set email alerts
|

Ag-doped ZnO nanorods embedded reduced graphene oxide nanocomposite for photo-electrochemical applications

Abstract: In this paper, the Ag-doped zinc oxide nanorods embedded reduced graphene oxide (ZnO:Ag/rGO) nanocomposite was synthesized for photocatalytic degradation of methyl orange (MO) in the water. The microstructural results confirmed the successful decoration of Ag-doped ZnO nanorods on rGO matrix. The photocatalytic properties, including photocatalytic degradation, charge transfer kinetics and photocurrent generation, are systematically investigated using electrochemical impedance spectroscopy (EIS), photocurrent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(38 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…To date, photocatalytic degradation using inorganic semiconductor nanomaterials has exhibited vast desirability and interest for researchers owing to its excellent physical and chemical properties such as low toxicity, electrochemical stability, super oxidative capacity, costeffectiveness, and environmental viability [2,8,9]. During the photocatalytic (PC) process, nanomaterials absorb greater visible light energy than bandgap initiated excitation between valence and conduction bands.…”
Section: Introductionmentioning
confidence: 99%
“…To date, photocatalytic degradation using inorganic semiconductor nanomaterials has exhibited vast desirability and interest for researchers owing to its excellent physical and chemical properties such as low toxicity, electrochemical stability, super oxidative capacity, costeffectiveness, and environmental viability [2,8,9]. During the photocatalytic (PC) process, nanomaterials absorb greater visible light energy than bandgap initiated excitation between valence and conduction bands.…”
Section: Introductionmentioning
confidence: 99%
“…The results of photocatalytic activity indicated an incompatible trend, meaning that the textural property was not the key factor determining the photocatalytic activity. Such a result was reported by Zhang et al and Khurshid et al It must be noted that the MPVA‐Alg has shown a proper thermal stability with good photocorrosion resistance, so it was not decomposed under UV irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…It is a two-dimensional planar structure with a thickness of a single layer to a few layers [1,2,3]. GO and its derivatives have been applied in soft electronics, functional composites, energy storage materials, medical equipment, gas sensor, and drug transportation [4,5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%